2021
DOI: 10.3390/ijms221910666
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of the RSH (RelA/SpoT Homologs) Gene Family and Expression Analysis in Response to PGPR Bacteria and Salinity in Brassica napus

Abstract: Among several mechanisms involved in the plant stress response, synthesis of guanosine tetra and pentaphosphates (alarmones), homologous to the bacterial stringent response, is of crucial importance. Plant alarmones affect, among others, photosynthetic activity, metabolite accumulation, and nutrient remobilization, and thus regulate plant growth and development. The plant RSH (RelA/SpoT homolog) genes, that encode synthetases and/or hydrolases of alarmones, have been characterized in a limited number of plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Thanks to the improvement of molecular biology and chemical biology techniques that imply that abiotic factors such as heavy metals may switch the production of natural compounds by modifying the attitude of secondary metabolism. The secondary metabolites produced by modern techniques like genome sequencing [ 7 ], abiotic or biotic stress [ 8 ], co-culture [ 9 ] and biosynthetic engineering proved to have enhanced pharmacological profiles compared to the compounds produced by the normal lab culture. Natural products have played an essential role in pharmacological and nutraceutical development [ 10 , 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the improvement of molecular biology and chemical biology techniques that imply that abiotic factors such as heavy metals may switch the production of natural compounds by modifying the attitude of secondary metabolism. The secondary metabolites produced by modern techniques like genome sequencing [ 7 ], abiotic or biotic stress [ 8 ], co-culture [ 9 ] and biosynthetic engineering proved to have enhanced pharmacological profiles compared to the compounds produced by the normal lab culture. Natural products have played an essential role in pharmacological and nutraceutical development [ 10 , 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 8-day-old seedlings of A. thaliana RSH3 -overexpression lines showed dwarf chloroplasts, metabolite reduction, and significantly inhibited plastid translation and transcription ( Maekawa et al, 2015 ). Previously, we showed that, in the presence of plant growth-promoting rhizobacteria, the expression level of BnRSH genes in canola seedlings significantly raised ( Dąbrowska et al, 2021b ), so it was surprising that in this study BnRSH1–3 and BnCRSH genes were unaffected or significantly downregulated in several experimental variants, including ones with T. viride ( Fig. 3 ).…”
Section: Discussionmentioning
confidence: 51%
“…Pharbitis nil (L.) Choisy) ( Dąbrowska, Prusińska & Goc, 2006 ). Plant RSH proteins have been proven to play a role in stress response to salinity ( Takahashi, Kasai & Ochi, 2004 ; Prusińska et al, 2019 ; Dąbrowska et al, 2021b ), drought ( Takahashi, Kasai & Ochi, 2004 ; Prusińska et al, 2019 ), darkness ( Ono et al, 2021 ), wounding, UV, heat shock, and pathogens ( Takahashi, Kasai & Ochi, 2004 ). Abdelkefi et al (2018) showed that, in A. thaliana , the accumulation of alarmones directly correlates with the susceptibility to turnip mosaic virus (TuMV) infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promoter analysis is a powerful tool that can provide an insight into the regulatory mechanisms of genes of interest. Moreover, studies on cis -regulatory elements (CREs) provide a foundation for future experiments 54 , 72 , 73 . Regulatory elements play a crucial role in plant responses to various stresses, including drought stress 74 .…”
Section: Resultsmentioning
confidence: 99%